2019
DOI: 10.1016/j.csda.2019.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the mean and variance of a high-dimensional normal distribution using a mixture prior

Abstract: This paper provides a framework for estimating the mean and variance of a highdimensional normal density. The main setting considered is a fixed number of vector following a high-dimensional normal distribution with unknown mean and diagonal covariance matrix. The diagonal covariance matrix can be known or unknown. If the covariance matrix is unknown, the sample size can be as small as 2. The proposed estimator is based on the idea that the unobserved pairs of mean and variance for each dimension are drawn fro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Considering the uncertainty of load from the perspective of load prediction deviation, the probability density distribution function of forecast deviation can be used for analysis. It is found that the normal distribution can better reflect the probability density distribution of load prediction deviation [24,25]. Therefore, a normal distribution is adopted here to describe the load prediction deviation, and its specific probability density distribution function is…”
Section: Load Uncertainty Modelmentioning
confidence: 99%
“…Considering the uncertainty of load from the perspective of load prediction deviation, the probability density distribution function of forecast deviation can be used for analysis. It is found that the normal distribution can better reflect the probability density distribution of load prediction deviation [24,25]. Therefore, a normal distribution is adopted here to describe the load prediction deviation, and its specific probability density distribution function is…”
Section: Load Uncertainty Modelmentioning
confidence: 99%